Management of metastatic endometrial cancer: physicians’ choices beyond the first line after approval of checkpoint inhibitors - Arezzo, Francesca; Giannone, Gaia; Castaldo, Daniele; Scotto, Giulia; Tuninetti, Valentina; Turinetto, Margherita; Bartoletti, Michele; Mammoliti, Serafina; Artioli, Grazia; Mangili, Giorgia; Salutari, Vanda; Lorusso, Domenica; et al. (Frontiers in Oncology, 2023)
Introduction: Endometrial cancer (EC) represents 3.4% of all newly diagnosed cancer cases and is responsible for 2.1% of all cancer-related deaths. Around 10-15% of women with EC are diagnosed with advanced-stage disease, resulting in a reported 5-year survival rate of only 17% for those with distant metastases. A better understanding of its molecular features has ushered in a new era of immunotherapy for the treatment of EC, allowing for alternative therapeutic approaches, even in cases of advanced disease.We administered a multi-choice online survey for Multicenter Italian Trials in Ovarian cancer and gynaecologic malignancies (MITO) members. The questionnaire was available for two months, starting in October 2022. Our objective was to evaluate the current attitude of incorporating molecular characterization of EC into routine clinical practice, appraise the implementation of newly available therapies, and compare the outcomes with the previous survey conducted in April-May 2021 to ascertain the actual changes that have transpired during this recent time period.The availability of molecular classification in Italian centers has changed in one year. The 75% of centers performed the molecular classification compared with 55.6% of the previous survey. Although this percentage has increased, only 18% performed all the tests. Significant changes have occurred in the administration of new treatments in EC patients in MITO centers. In 2022, 82.1% centers administrated dostarlimab in recurrent or advanced MMR deficient (dMMR) EC experiencing disease progression after platinum-based chemotherapy regimens, comparing to only 24.4% in 2021. In 2022, 85.7% centers already administrated the association pembrolizumab plus lenvatinib in secondline for MMR proficient (pMMR) patients with advanced or recurrent EC who had progressed on firstline platinum-based therapy.Conclusions: Both the therapeutic and diagnostic scenario has changed over the last couple of years in MITO centers, with an increased prescription of immune checkpoint inhibitors and use of the molecular classification.